2015
DOI: 10.1002/berj.3188
|View full text |Cite
|
Sign up to set email alerts
|

The role of aspirations in young children's emotional and behavioural problems

Abstract: Using data from a large UK cohort (n = 11,656), we investigated the determinants of 7-year-old children's aspirations, and the role of these aspirations in emotional and behavioural problems, as reported by both parents and teachers. Aspirations were classified to reflect their occupational status, masculinity/femininity and intrinsic/extrinsic motivation. Children's aspirations had significant antecedents in social disadvantage, parental involvement in learning, parental values and cognitive ability. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…Evidence examining the link between own and others’ aspirations is sparse, but that which exists suggests that parents’ values and aspirations are meaningfully associated with the aspirations of their children (Chew & Wang, 2010; Henderson‐King & Brooks, 2009; Kasser, Ryan, Zax, & Sameroff, 1995; Moulton, Flouri, Joshi, & Sullivan, 2015; Roman et al, 2015; Soenens et al, 2015). The children of mothers who endorse extrinsic aspirations experience pressure to pursue extrinsic aspirations themselves (Soenens et al, 2015), and parents (the samples usually comprise mostly mothers) who value popularity have more extrinsically oriented children (Moulton et al, 2015). Furthermore, children’s own valuing of aspirations for personal growth, affiliation, and financial success has been associated with the extent to which their mothers valued those aspirations (Kasser et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence examining the link between own and others’ aspirations is sparse, but that which exists suggests that parents’ values and aspirations are meaningfully associated with the aspirations of their children (Chew & Wang, 2010; Henderson‐King & Brooks, 2009; Kasser, Ryan, Zax, & Sameroff, 1995; Moulton, Flouri, Joshi, & Sullivan, 2015; Roman et al, 2015; Soenens et al, 2015). The children of mothers who endorse extrinsic aspirations experience pressure to pursue extrinsic aspirations themselves (Soenens et al, 2015), and parents (the samples usually comprise mostly mothers) who value popularity have more extrinsically oriented children (Moulton et al, 2015). Furthermore, children’s own valuing of aspirations for personal growth, affiliation, and financial success has been associated with the extent to which their mothers valued those aspirations (Kasser et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of parent and child aspirations have been conducted primarily in Western countries such as the United States (Kasser et al, 1995), the United Kingdom (Moulton et al, 2015), and Belgium (Soenens et al, 2015). While the benefits of relative intrinsic aspiring and the disadvantages of relative extrinsic aspiring have been established in diverse cultures and nations (e.g., Kim, Kasser, & Lee, 2003; Ryan et al, 1999), to our knowledge, only two studies have utilized Japanese samples (Kitamura, Kijima, Takeuchi, & Tomoda, 2014; Nishimura & Suzuki, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Beal and Crockett (2010) found that career aspirations in adolescence were not related to either of their measures of problem behaviour (i.e., delinquency and substance use). By contrast, Moulton, Flouri, Joshi, and Sullivan (2015b) found that low career aspirations were related to emotional problems in young children, and Boxer, Goldstein, Delorenzo, Savoy, and Mercado (2011) found that adolescents' high academic aspirations were associated with less antisocial behaviour. Studies taking a psychological theory approach to classifying children's and adolescents' aspirations have been more successful in finding associations with psychological adjustment than those measuring aspirations solely by their prestige.…”
Section: Children's Aspirations and Emotional And Behavioural Problemsmentioning
confidence: 92%
“…Their cognitive and perceptual ability, maturity all are growing quickly in a healthy built environment where they live, enjoy, grow and develop. Furthermore, children of this age group start to gain basic social valuation and personal characteristics (Moulton et al, 2015). In this context, this study has selected the cases from class 5 and class 8 school going children from three high schools of Khulna city, Bangladesh, namely (i) Khulna Zilla School; (ii) Government Coronation Girls High School; and (iii) Lions School based on their reputation, year of establishment and gender dimensions.…”
Section: Methods Of the Studymentioning
confidence: 99%